Aplicação de ultrassom e água eletrolisada básica na elaboração de linguiça frescal com reduzido teor de NaCl - Seibt, Ana Carolina Mendes Dias (2023)
Fresh sausages are perishable foods and the reduction of the NaCl content in their composition reduces shelf life due to the growth of microorganisms. In the present study, the influence of different concentrations of NaCl (from 2.5% and 1.75%), action of basic electrolyzed water (AEB) (0.02%) and ultrasound (US) (25 kHz, 80% of amplitude, 159 W, sweep mode 20 min), totaling 08 treatments, which physical-chemical (pH, redox potential and water activity), microbiological (mesophilic, psychotrophic, lipolytic, enterobacterial and lactic), oxidative (Tbars), formation of nitrous pigments, fatty acid profile of the control treatment with 100% NaCl, evaluation of volatile compounds, texture and sensory analysis at three different times of shelf life (1st, 15th and 30th day). The results showed that in the centesimal composition of sausages, all treatments met current legislation. The pH showed a higher value in products containing 1.75% NaCl and AEB (6.27-5.91) and a lower redox potential (Eh) (50-22.50 mV). In water activity (Aw) all values found were similar (0.96 – 0.97). In the analysis of TBARs (0.016 – 0.134 mg MDA), the lowest values identified were in the treatment with 1.75% of NaCl and BEW and also found greater formation of nitrous pigments (43 – 51 ppm). In the microbiological analyses, the counts of mesophilic (3.33 – 4.16 log UFC/g) and psychrotrophic (3.89 – 6.73 log) bacteria were lower in sausages with 2.50% NaCl up to the 15th day of storage. Mesophilic lactic bacteria (2.08 - 6.69 log UFC/g) grew less than psychrotrophic lactic bacteria (2.53 - 3.75 log UFC/g) at 1.75% NaCl during storage. On the other hand, the counts of lipolytic bacteria (4.65 - 6.69 log UFC/g) and enterobacteria (2.08 - 3.42 log UFC/g), showed the same growth behavior in all treatments. The sensory profile of the fresh sausage was traced through the Quantitative Descriptive Analysis (QDA), emphasizing the treatment with sonicated NaCl reduction, with the addition of basic electrolyzed water (TUSBEW70) which showed a high correlation (with such and such abribute) that was maintained in the day 1 and 30º of shelf life, associated with the use of US and BEW for the reduction of NaCl. In the texture profile, the reduction of NaCl and the use of US demonstrated that sonicated meat products present a better distribution of salt, and in the TUSBEW70 treatment, the sausages were characterized as softer both on the 1st day and on the 30th day of storage. In CONTROL100, oleic acid (C18:1-cis(n9) (34.85 ± 2.42) was the major compound in the sample, which acts to help reduce non-transmissible chronic diseases, such as cardiovascular diseases. In the analysis of volatile compounds, the 30% reduction of NaCl in the formulation of products in general reduced the compounds originating from lipid oxidation, such as heptanal, hexanal and pentanal identified in the samples. At the beginning of storage, the action of the basic electrolyzed water in the treatments can be seen. Therefore, this product can be inserted in the meat products market, based on the use of clean technologies and reduction of salt content, with greater healthiness for consumers.